Rising report of Plasmodium vivax in sub-Saharan Africa: Implications for malaria elimination agenda - Mary Aigbiremo Oboh (Scientific African, 2020)
Plasmodium vivax and P. falciparum are the most important human malaria species. P. falciparum is considered the most virulent and widespread species in sub-Saharan Africa. Hence, control efforts have focused on reducing the morbidity and mortality associated with falciparum malaria. However, with improved malaria diagnostics, there is more evidence of high vivax burden in Africa. As P. vivax is capable of dormancy in the liver, it is suspected that artemisinin-based combination treatment widely use across Africa to combat falciparum malaria may be favouring adaptive selection for P. vivax. Additionally, a better understanding of the mechanism of erythrocytes invasion in Duffy-negative individuals who were previously believed to be protected against P. vivax is needed. Therefore, this review discusses the epidemiological implications of P. vivax and P. falciparum co-endemicity in Africa. We also examine available tools for diagnosis of vivax malaria. We conclude by recommending specific interventions against P. vivax that can impact current malaria elimination strategies.